KADAR KALSIUM, DAYA KEMBANG, DAN SIFAT ORGANOLEPTIK KERUPUK ONGGOK SINGKONG DENGAN VARIASI PENAMBAHAN TEPUNG CANGKANG RAJUNGAN (Portunus pelagicus) - Kurnia Abadi Mustofa; Agus Suyanto (Universitas Muhammadiyah Semarang, 2011)
Shell Crab (Portunus pelagicus) has a high mineral content, particularly calcium (19.97%). The content of crab shell is a potential for flouring and used as a food additive calcium source. Onggok cassava’s has the potential to be used as raw material for the used of crackers. The research objective was to determine the levels of calcium, ability to swell, and organoleptic properties of Onggok cassava’s crackers with the addition of flour shell crab. Variations addition of flour shell crab taken is 0%, 10%, 20%, 30%, and 40%. The results are significantly for calcium, ability to swell, and organoleptic properties. Highest calcium levels at a concentration of 40% ie 3,267 mg/100 g. The ability of swell is highest at 30.73% control. The result: the best flavor in the control, but the addition of flour shell crab is acceptable to used the crackers.